Prosedur Gadai Emas dalam Menjamin Kepastian dan Perlindungan Hukum - Melky Lolowang; Paula; Andyna Susiawati Achmad (CV Rewang Rencang, 2025)
This paper discusses the proper gold pawn procedure to protect creditors and legal protection for PT Pegadaian against third-party gold pawn objects. Research on this gold pawn procedure provides an overview of how gold pawn is formed that is in accordance with the principles of contract law and the legal requirements of an agreement when compared to the distribution and settlement/auction mechanism for gold pawn products at PT Pegadaian. Ownership of movable objects, in this case gold pawn collateral, refers to Article 1977 of the Civil Code which states that anyone who brings movable objects is considered the owner of the movable objects and is entitled to carry out legal acts, including gold pawn transactions in. Meanwhile, legal protection for PT Pegadaian against third-party gold pawn objects provides an overview of risk mitigation efforts before the distribution of gold pawn products and legal steps after legal problems occur at PT Pegadaian. The legal basis of PT Pegadaian contained in the Financial Services Authority Regulation Number 31 of 2016 and others provides legal certainty and legal protection for PT Pegadaian as a creditor in carrying out company operations and distributing gold pawn products to the public.